La contravención penal y las medidas de protección previa a la audiencia de juzgamiento - Núñez Hernández, Jessica Anabel (2019)
The Constitution of the Republic of the Ecuador in 2008, gave a total twist, so it's obvious changes policy, being highly protective of principles and constitutional rights; What, his conviction is participatory, the voice of the people is strength, decisions that the Ecuadorian community take to prevail, becoming law. When we refer to the rights do, justice administrators have duty guardianship of preserving the integrity of persons; so, it is necessary to have knowledge of incidents between citizens are or not of public shock, its obligation is to maintain order and legal certainty. The incidents between citizens can differentiate between offences and infringements, these actions must be precauteladas by the competent authorities, that these acts to be established within that regulates the actions of persons, they will have to receive the sanction that corresponding according to the extent of the damage, safeguarding a citizen total integrity, whether they are victims or aggressors….